Pocket book of technical writing for engineers and scientists - Finkelstein, Leo, 1946- (New York, N.Y : McGraw-Hill Higher Education, 2008)
Aims to teach engineering students the skill of technical writing. This book uses practical outlines throughout, and shows students how to produce the technical documents in a manner that is fun and interesting to students. It contains chapters which feature an end-of-chapter critique that allows students to implement what they have learned.
Introduction -- Ethical Considerations -- Technical Definition -- Descriptions of a Mechanism -- Descriptions of a Process -- Proposals -- Progress Reports -- Feasibility and Recommendation Reports -- Laboratory and Project Reports -- Instructions and Manuals -- Research Reports -- Abstracts and Summaries -- Grammar, Style, and Punctuation -- Documentation -- Visuals -- Electronic Publishing -- Presentations and Briefings -- Business Communications -- Resumes, Cover Letters, and Interviews -- Team Writing Index
Includes bibliographical references and index.
Keywords: Technical writing -- Handbooks, manuals, etc